Postural load management methods to reduce skeletal muscle disorders in lifting maneuvers - Sosa Pacheco, Nilo Ronald (2023)
The objective of the study was to determine the influence of postural load management through the joint evaluation of the REBA and OWAS method in an evaluation matrix in lifting maneuvers on the reduction of musculoskeletal disorders. It was directed in a quantitative study, experimental design, applied and sample of 52 operators; the instruments were the Kuorinka Nordic questionnaire, ergonomic evaluation form, REBA and OWAS integrated evaluation matrix, ergonomic control monitoring matrix and ergonomic satisfaction questionnaire. The results indicated that the expectation of postural management at the beginning was 90.4% dissatisfaction and when jointly evaluating REBA and OWAS, 98.1% satisfaction was reached (p=0.000); Regarding medical rest due to ailments, there was 9.6% in 2019 and between 2020-2021 there was no evidence of any; while work absenteeism decreased, in 2019 it was 21.2%, in 2020 it was 15.4% and in 2021 it was 0% (p=0.000); In addition, both methods, REBA and OWAS, demonstrated concordance (t=0.7, p=0.000). It was concluded that the REBA and OWAS method contribute to the improvement of postural load management, reduce musculoskeletal disorders and detect postural problems, allowing preventive and corrective actions to be carried out.